KENDALA-KENDALA YANG DIHADAPI MASYARAKAT MISKIN DALAM MENGAKSES PENDIDIKAN FORMAL (Studi pada Keluarga Pemulung di Kelurahan Gunung Sulah Kecamatan Way Halim Kota Bandar Lampung) - Budi, Endik Arya; Sidemen, I Gede (JURNAL SOSIOLOGI, 2013)
This research aimed at described constraints that have been faced by poor people, especially the family scavengers of gunung sulah for accessing formal education. Type this research is descriptive with a qualitative approach with a method of collecting data done by means of an interview deep and observation. Engineering analysis of data done by means of the reduction of data, presentation of data, and the withdrawal of the conclusion. The results showed that a scavenger that is in gunung sulah entirely live below the poverty line, so that they must work harder to her child can school, don t even rarely drop out of school was due to the absence of the cost. The obstacles faced by the family scavengers for accessing formal education are very diversified, some of them are parents a scavenger that low income levels, bustle parents in fulfilling the necessities of life, absence of time children, parents in the process of education the community about that is not conducive, and an apathy and individualist, among the members of society and a government policy that was not efficient. Â Keywords: scavenger, access to education, dropout